2007
DOI: 10.1016/j.immuni.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Produced Transforming Growth Factor-β1 Controls T Cell Tolerance and Regulates Th1- and Th17-Cell Differentiation

Abstract: TGF-beta1 is a regulatory cytokine with a pleiotropic role in immune responses. TGF-beta1 is widely expressed in leukocytes and stromal cells. However, the functions of TGF-beta1 expressed by specific lineages of cells remain unknown in vivo. Here, we show that mice with a T cell-specific deletion of the Tgfb1 gene developed lethal immunopathology in multiple organs, and this development was associated with enhanced T cell proliferation, activation, and CD4+ T cell differentiation into T helper 1 (Th1) and Th2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
534
2
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(569 citation statements)
references
References 50 publications
24
534
2
9
Order By: Relevance
“…Treg can interact with other immune populations via soluble factors and/or via cell-contactdependent mechanisms. Whereas in vivo studies have suggested a major role for soluble factors, such as IL-10 [41], TGF-b [42], or IL-35 [43], most in vitro experiments described a cell-contactdependent mechanism, involving CTLA-4 [44,45], GITR [46], Perforin [33], or Granzyme B [34]. Our data suggest that Perforin/ Granzyme-induced apoptosis does not play a major role in Tregmediated suppression of mouse gd-T-cell activity.…”
Section: Discussionmentioning
confidence: 52%
“…Treg can interact with other immune populations via soluble factors and/or via cell-contactdependent mechanisms. Whereas in vivo studies have suggested a major role for soluble factors, such as IL-10 [41], TGF-b [42], or IL-35 [43], most in vitro experiments described a cell-contactdependent mechanism, involving CTLA-4 [44,45], GITR [46], Perforin [33], or Granzyme B [34]. Our data suggest that Perforin/ Granzyme-induced apoptosis does not play a major role in Tregmediated suppression of mouse gd-T-cell activity.…”
Section: Discussionmentioning
confidence: 52%
“…Human Treg although expressing weak TLR2 respond to agonist heat shock protein HSP60 [29,30]. To discriminate whether CD1c 1 MoLC or induced Treg are the crucial source for TGF-b and thereby for Th17 induction in our cultures, we blocked TLR2 on CD1c 1 MoLC before coculturing them with CD4 1 T cells.…”
Section: Blocking Tlr2 On Pgn-stimulated Molc Prevents Th17 Differentmentioning
confidence: 99%
“…In contrast, IL-27 also uses gp130 as signalling subunit but this cytokine acts as an immunosuppressor or a Th1-inducer and inhibits the promotion of a Th17 immune response [19]. The regulation of the different Th subsets is done by Treg and their development and function are regulated by TGF-b1 and the transcription factor Foxp3 [20,21]. Since TGF-b1 is a common factor for Treg and Th17 cells, it is possible that a switch from Th17 to Treg exists in vivo in the absence of IL-6 signalling in T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Development of naïve T cells to Th17 cells requires the presence of IL-6, TGF-b1 and the transcription factor RORgt [14][15][16][17]. [20,21]. Since TGF-b1 is a common factor for Treg and Th17 cells, it is possible that a switch from Th17 to Treg exists in vivo in the absence of IL-6 signalling in T cells.…”
mentioning
confidence: 99%